Kekerasan Non-fisik Media pada Artis Gisella Anastasia (Analisis Wacana Kritis Sara Mills) - Bungsu, Agung Pangeran (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2021)
Abstract: The increasing violence against women makes the issue of gender will continue to be interesting to study. The forms of violence committed against women are also increasingly diverse, one of which is non-physical violence through the news media. Women are often treated unfairly and even harassed their dignity in news discourse. This paper will describe the styles of two media that are quite popular in Indonesia, namely Detik.com and Media Indonesia in constructing news about the hot video of artist Gisella Anastasia. Then the discourse construction will be analyzed using Sara Mills' critical discourse analysis. Sara Mills' critical discourse analysis will analyze the discourse building holistically which includes the position of the subject-object and also the position of the writer-reader in the news. The results of the study reveal that the position of the subject and the author is dominated by men to convince the public that women are the cause of the hot video case. The tendentious narratives aimed at women by the two media in constructing discourse further exacerbate the framing inherent in women. Keywords: Gisella Anastasia, Sara Mills Critical Discourse Analysis, Sara Mills Critical Discourse Analysis Abstrak: Meningkatknya kekerasan pada perempuan membuat isu tentang gender akan terus menarik untuk dikaji. Bentuk kekerasan yang dilakukan pada perempuan juga semakin beragam, salah satunya kekerasan non fisik lewat media pemberitaan. Perempuan kerap diperlakukan tidak adil bahkan dilecehkan martabatnya dalam pewacanaan berita. Tulisan ini akan menguraikan gaya dua media yang cukup populer di Indonesia yaitu Detik.com dan Media Indonesia dalam mengkonstruksikan berita tentang video panas artis Gisella Anastasia. Kemudian konstruksi wacana akan dianalisa dengan menggunakan analisis wacana kritis Sara Mills. Analisis wacana kritis Sara Mills akan menganalisa bangunan wacana secara holistik yang meliputi posisi subjek-objek dan juga posisi penulis-pembaca dalam pemberitaan. Hasil penelitian mengungkapkan posisi subjek maupun penulis dikuasai oleh laki-laki untuk meyakinkan publik bahwa perempuan sebagai penyebab terjadinya kasus video panas. Narasi tendensius yang ditujukan bagi perempuan oleh kedua media dalam mengkonstruksikan wacana semakin memperburuk framing yang melekat pada perempuan. Kata Kunci: Gisella Anastasia, Analisis Wacana Kritis Sara Mills, Critical Discourse Analysis Sara Mills